Exploring multiliteracies competencies in Indonesian teacher education: a cross-disciplinary survey of pre-service teachers - Andriyati, Nofica; Amin, Abdul; Li, Yanping (Frontiers in Education, 2025)
IntroductionThis study investigates the multiliteracy competence and pedagogical readiness of pre-service teachers in Indonesia, with a particular focus on their ability to implement multimodal pedagogy. It examines differences in three key areas: (1) conceptual multiliteracy knowledge, (2) pedagogical preparedness for designing multimodal instruction, and (3) perceptions of challenges in implementing multiliteracy.MethodsA quantitative survey approach was employed to collect data from pre-service teachers enrolled in both language-related programs (e.g., English, Arabic education) and non-language programs. The relationships between Pedagogical Content Knowledge for Multiliteracies (PCKM) and multiliteracy frameworks were analyzed using Confirmatory Factor Analysis (CFA).ResultsThe study identified significant differences between language-related and non-language program participants in terms of preparedness and knowledge. The findings contribute to an expanded understanding of multiliteracy in teacher education, particularly within developing countries such as Indonesia, which presents a unique context due to its cultural diversity, complex social dynamics, and regional disparities in digital access.DiscussionThese results offer practical recommendations for redesigning teacher education curricula, enhancing pre-service teachers’ readiness to integrate multimodal pedagogy, addressing the specific challenges they face, and developing culturally and contextually relevant multiliteracy assessment tools.